E3 ubiquitin ligase MAGI3 degrades c-Myc and acts as a predictor for chemotherapy response in colorectal cancer - Haibo Wang; Wenjing Yang; Qiong Qin; Xiaomei Yang; Ying Yang; Hua Liu; Wenxiu Lu; Siyu Gu; Xuedi Cao; Duiping Feng; Zhongtao Zhang; Junqi He (Molecular Cancer, 2022)
Abstract Background Recurrence and chemoresistance constitute the leading cause of death in colorectal cancer (CRC). Thus, it is of great significance to clarify the underlying mechanisms and identify predictors for tailoring adjuvant chemotherapy to improve the outcome of CRC. Methods By screening differentially expressed genes (DEGs), constructing random forest classification and ranking the importance of DEGs, we identified membrane associated guanylate kinase, WW and PDZ domain containing 3 (MAGI3) as an important gene in CRC recurrence. Immunohistochemical and western blot assays were employed to further detect MAGI3 expression in CRC tissues and cell lines. Cell counting kit-8, plate colony formation, flow cytometry, sub-cutaneous injection and azoxymethane plus dextran sulfate sodium induced mice CRC assays were employed to explore the effects of MAGI3 on proliferation, growth, cell cycle, apoptosis, xenograft formation and chemotherapy resistance of CRC. The underlying molecular mechanisms were further investigated through gene set enrichment analysis, quantitative real-time PCR, western blot, co-immunoprecipitation, ubiquitination, GST fusion protein pull-down and immunohistochemical staining assays. Results Our results showed that dysregulated low level of MAGI3 was correlated with recurrence and poor prognosis of CRC. MAGI3 was identified as a novel substrate-binding subunit of SKP1-Cullin E3 ligase to recognize c-Myc, and process c-Myc ubiquitination and degradation. Expression of MAGI3 in CRC cells inhibited cell growth, promoted apoptosis and chemosensitivity to fluoropyrimidine-based chemotherapy by suppressing activation of c-Myc in vitro and in vivo. In clinic, the stage II/III CRC patients with MAGI3-high had a significantly good recurrence-free survival (~ 80%, 5-year), and were not necessary for further adjuvant chemotherapy. The patients with MAGI3-medium had a robustly good response rate or recurrence-free survival with fluoropyrimidine-based chemotherapy, and were recommended to undergo fluoropyrimidine-based adjuvant chemotherapy. Conclusions MAGI3 is a novel E3 ubiquitin ligase by degradation of c-Myc to regulate CRC development and may act as a potential predictor of adjuvant chemotherapy for CRC patients. Graphical Abstract